(untitled) (Global Journal of Human-Social Science, 2015)
This study is stating the political and socio-economic rights on the conditions of women in the municipalities of KounkanÃ© and DiaobÃ©-Kabendou Department of VÃ©lingara, Senegal. Method: The study was made during the month of May 2013.After a documentary of policies and guidelines on the political and economic rights of women in terms of women’s access to land and water a quantitative and qualitative, aresearch from questionnaire, interview and focus group was made. Depending on the type of research, software Epi- info and SPSS were used to capture, control, validate and analyse data. Results:The study was made with 448 women within the women’s promotion group or not, leaders or not, with an age ranging from 18 to 92 years. Pular (69%) constitute the majority ethnic. 85.5% of women were married. 40.60% of women were not educated, 48.80% of women were farmer. However, 35.5% were satisfied with the area. They reported acquire farmland mainly from their husbands (45.40%) and by inheritance (23.6%). Generally, Small businesses (44.4%) and household activities (29.5 %) were womenâ€™s occupations. 56.5% of women had a national identity and voter registration card. 60.90% of couples make decisions together. 28.90% of women belonged to decision-making bodies. 57.1% of women had experienced violence, 73.40% of them were aware of the help and assistance structures. However, concerning violence within couples, 64% of abused women within the couple noted a change in attitude after mediation. F a mily (43.1%) and the district chief or notable (32.8%) are the remedies most famous women. Conclusion: Despite the positive development of human rights in Senegal, many actions are to be undertaken in the municipalities of KounkanÃ© and DiaobÃ©-Kabendou for the reality gap is known and fought for and that women enjoy and exercise, like men, fundamental rights recognized for good health to the person regardless of their gender.